2020
DOI: 10.3390/coatings10050485
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Numerical Study on Friction Reduction and Wear Resistance by Surface Coating on Cam/Tappet Pairs under Different Conditions

Abstract: As a vital component in the valve train of internal combustion engines (ICEs), the cam/tappet pair undergoes high mechanical and thermal loads and usually works in a mixed and boundary lubrication regime. This leads to considerable friction loss and severe surface wear. Currently, the applications of diamond-like carbon (DLC) coatings for automotive components are becoming a promising strategy to reduce the friction and lower the wear. However, the practical performance of the coating is related to many factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…As already described in other papers on cam-tappet contact, there are pronounced mixed friction conditions over the entire cycle. The resulting friction force results mainly from the solid contact for all load cases considered, as was also the case in the studies of LYU [32] for similar surface properties. The majority of the friction is accounted for by the cam tip contact.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As already described in other papers on cam-tappet contact, there are pronounced mixed friction conditions over the entire cycle. The resulting friction force results mainly from the solid contact for all load cases considered, as was also the case in the studies of LYU [32] for similar surface properties. The majority of the friction is accounted for by the cam tip contact.…”
Section: Discussionsupporting
confidence: 58%
“…When investigating the surface roughness, it becomes obvious that even small deviations have a tremendous effect on the tribological behavior in the contact. The high influence of the surface asperities on the tribological behavior was also presented by LYU [32]. The consideration of the roughness in the simulation is thus essential, as, otherwise, the real mixed friction conditions are not represented correctly.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A reduction of 45% in friction torque was observed when using a ta-C coating compared with the result for a conventional phosphate coating on carburized steel at an engine speed of 2000 rpm [46]. A novel multiphysics analytical model considering the mechanical, thermal, and tribological properties of DLC coatings was proposed by Lyu et al [52], and their simulation results predicted a reduction in friction loss of up to 45% within a cam cycle of the DLC-coated (a-C:H) cam/tappet under a heavy engine load. Even though the wear condition became progressively more severe as the ambient temperature increased, the wear resistance of the DLC coatings was still impressive.…”
Section: Low-friction Bearings and Valve Trainsmentioning
confidence: 99%
“…10 Lyu et al used the micro-convex model 11 to describe the roughness and examined the tribological characteristics of the coated cam-tappet. 12 Their results indicated that the coating may lessen friction loss.…”
Section: Introductionmentioning
confidence: 99%